Rhein for treating diabetes mellitus: A pharmacological and mechanistic overview - Deng, Tingting; Du, Jinxin; Yin, Ying; Cao, Baorui; Wang, Zhiying; Zhang, Zhongwen; Yang, Meina; Han, Jinxiang (Frontiers in Pharmacology, 2023)
With the extension of life expectancy and changes of lifestyle, the prevalence of diabetes is increasing by years worldwide. Rheum palmatum L., a natural botanical medicine, has been used for thousands of years to prevent and treat diabetes in eastern countries. Rhein, the main active component of Rhubarb, is a 1, 8-dihydroxy anthraquinone derivative. Previous studies have extensively explored the clinical  application value of rhein. However, comprehensive review of the antidiabetic effects of rhein have not been conducted. This study summarizes the studies published over the past decade on the antidiabetic effects of rhein, covering the biological characteristics of Rheum palmatum L., pharmacological effects of rhein, and its pharmacokinetic characteristics. This study shows that rhein can prevent and treat diabetes by ameliorating IR, anti-inflammatory, anti-oxidative stress, and protecting islet cells, which provides a theoretical basis for further application of rhein.